PERTANIAN MAJU DAN BERKUALITAS DI DESA SEMBALUN KECAMATAN SEMBALUN LOMBOK TIMUR: Advanced And Quality Agriculture In Sembalun Village, Sembalun District, East Lombok - Haryantini, Baiq Azizah; Haryanto, Hery; Sunantra, I Made; Wardhana, Agung Widya; Arifin, Zainal; Baharuddin, Baharuddin; Zainab, Siti; Apzani, Wawan (Yayasan Al-Amin Qalbu, 2023)
Organic farming is an agricultural system that only uses materials available in nature as production inputs, both in terms of fertilizers and pesticides. Currently, people's need for organic food is becoming higher so its availability needs to be increased. The obstacle in this activity is the lack of interest of farmers in carrying out organic plant cultivation because the harvest is smaller and the handling is more specialized compared to regular farming. This activity aims to educate farmers so that they want to switch to becoming better quality organic farmers so that they can improve the quality of life of the community and the economic value of farmers. Apart from that, the use of additional organic fertilizer which functions as a source of nutrients for plant growth, local microorganisms Trichoderma spp. as a bioactivator and biological control agent, it will be able to reduce the need for fertilizer and pesticides in the production phase so that advanced and quality agriculture in Sembalun Village can be realized